Process of Peace Building through Female Roles in the Circumstance of Violence in Asia: A Case Study of Aceh Province, Indonesia and Deep South of Thailand - Tissamana, Apinya (King Prajadhipok’s Institute Journal, 2021)
The study "Process of Peace Building through Female Roles in the Circumstance of Violence in Asia” aims at analyzing the female roles in Asia in the resolutions of the violence and conflicts through the peace process. This qualitative research is to raise an awareness in the form of policy proposal to the government and related organizations. The empirical data are applied to this study to form understandings and operations among women's organizations and peace networks in resolving political and gender-based violence.To access the peace process, the researcher includes the case study to gather information through both documents and interviews in the field to learn the experiences, knowledge, and abilities of the women from various organizations working as leaders of the peace process in Aceh, Indonesia and Deep South of Thailand. The study found that women are affected with violence as victims of war and insurgency with weapons. Due to the losses, there is unification of women who have lost family members and those who are affected. These women have also considered the further consequence of violence. For example, the acts of violence will be more common in the area of conflicts where women are bearing the burden of doing both housework and social work.If the operation is run by the state, the female community and organizations will be excluded in decision-making on the direction of the society. Moreover, this research has found a suggestion to organize a female group to resolve the conflicts in the family which overlap in the conflict area within the society. The activities occur during working time among social groups who identify the problems together and this is depending on social factors such as politics, environment, cultures, belief, religions, and interpretation of ethnicity.The forms of conflicts then lead to women's roles and participation in the peace process in Aceh Province, Indonesia and in Deep South of Thailand.